Design and Implementation of Network and Server Monitoring Using Zabbix at The Financial and Development Supervisory Agency - Irianto, Denna; Yasin, Verdi; Sianipar, Anton Zulkarnain (Jurnal Teknologi Informatika dan Komputer, 2025)
In today's digital era, network and server reliability are key factors in the smooth operation of an organization/institution. The Financial and Development Supervisory Agency (BPKP), as an institution that carries out government duties in the field of financial and development supervision, requires an efficient monitoring system to ensure the continuity of services and security of IT infrastructure to maintain the sustainability of the audit system, consultation, assistance, and evaluation of the results of supervision that will be reported to the President as Head of Government. The Financial and Development Supervisory Agency (BPKP) requires a good network and server monitoring system to maintain the availability and performance of IT services. The problem faced is the lack of real-time visibility into the condition of the IT infrastructure, which can hinder early detection of system disruptions or anomalies. This research aims to design and implement a network and server monitoring system using Zabbix as an open-source solution that is able to monitor performance, availability, and provide automatic notifications when failures occur. The methods used include literature review, needs analysis, system architecture design, Zabbix Server and Agent implementation, and system testing in the BPKP environment. The implementation results show that Zabbix is capable of providing comprehensive data visualization, real-time monitoring, and an effective alert system. In conclusion, the implementation of Zabbix has successfully increased efficiency in IT infrastructure management at BPKP and can be used as a basis for developing broader monitoring for all BPKP representatives.